Preparatory Operation of Automated Distribution Systems for Resilience Enhancement of Critical Loads - Nguyen, Hieu Trung; Muhs, John; Parvania, Masood (IEEE transactions on power delivery, 2021)
This paper proposes a stochastic optimization model for preparatory operation of distributed energy resources that enhance the resilience of critical loads against extreme weather events. Adopting hurricanes as a case study of extreme weather events, a high-precision spatio-temporal hurricane impact analysis model is first developed to enhance the situational awareness of automated distribution systems and generate a set of hurricane-induced outage scenarios. A stochastic mixed-integer conic programming model is then developed for co-optimizing the preparatory schedule of distributed energy storage and distributed generation ahead of hurricane along with post-event decisions of restoring services to customers, while minimizing the expected cost of energy not served as the index to measure the resilience. The proposed model prioritizes the service restoration of critical loads by integrating customer interruption cost function, which captures the customer type and outage costs as well as interruption duration in making restoration decisions. Additionally, a conic power flow model is adopted to accurately capture network operation constraints in pre- and post-outage scenarios. Numerical results conducted on the IEEE 33-bus system show that the proposed model can enhance the performance of automated distribution systems in responding to hurricane-induced outages by efficiently utilizing grid resources to improve the resilience of critical loads.